Design Build Temperature and Humidity Monitoring Internet of Things based for Optimization Oyster Mushroom Growth - Muhlasah Novitasari Mara; Catur Budi Waluyo; Alsah Nur Laila; Sasya Puteri Setyahadi; Sarono Widodo; Abu Hasan; Thomas Agung Setiawan; Budi Basuki Subagio (Politeknik Negeri Semarang, 2026)
Oyster mushroom (Pleurotus ostreatus) cultivation in Indonesia faces challenges in maintaining stable temperature and humidity in the growing room, particularly because monitoring is still performed manually, which increases the risk of errors. To address this issue, Sasya Puteri Setyahadi and Alsah Nur Laila designed an Internet of Things (IoT)-based temperature and humidity monitoring system that can be accessed in real time and remotely. The system uses the SHT31 sensor for data acquisition, an ESP32 microcontroller as the main processor, and the Firebase platform for data storage and visualization. Data are displayed through a web application and are integrated with an automatic watering response when parameter values fall outside the optimal range of 16–30 °C for temperature and 80–95% for humidity. Testing results showed that the system is capable of reading and transmitting data accurately and quickly. The main contribution of this study is the development of an environmental monitoring system for oyster mushroom cultivation with an automatic notification feature based on threshold values, which can serve as a foundation for future automated control systems. Comparative testing showed that the SHT31 sensor had an average temperature measurement error of 1.427% (accuracy 98.573%) and an average humidity measurement error of 2.017% (accuracy 97.983%) compared to the HTC-1 reference instrument. Meanwhile, the JSN-SR04T water level sensor achieved an average error of 2.076% (accuracy 97.924%). Furthermore, the system demonstrated an average data transmission delay of 1488.89 ms and an average jitter of 11.588 ms. Overall, the high accuracy across tests, combined with relatively low delay and jitter values, indicates that the system performs effectively and reliably in maintaining the mushroom house environment within the ideal range required to support optimal oyster mushroom growth.